Maternal Care and Attachment Security in Preschool Children - Magaly Nóblega; Patricia Bárrig; Katherine Fourmen (Psicologia: Teoria e Pesquisa)
Abstract This study assessed and compared the relationship between maternal sensitivity and child attachment in two groups of mother-child dyads from Lima, Peru, one group with children 4 years old and older and a second group with younger children. Fifty-six dyads participated in the study. The mothers ages ranged between 22 and 45 years (M = 33.14, SD = 5.50); 82.1% of them had higher education and 73.2% were in a partner relationship. Of the children, 53.6 were boys and 41.1% were an only child. The study used AQS and MBPQS to rate child and maternal behavior respectively. Our results show a high correlation between attachment security and maternal sensitivity in both groups, as well as specific manifestations of these variables in the context studied.